Measuring Usability of Phonic Mobile Applications based on User Success Rate for Pre-School Children - Carolyne, Alphonsus Tommy; Jacey-Lynn, Minoi (2016)
Recent studies showed that mobile devices have the potential to support children's learning and have increased the interest of parents and educators. However, it is important that mobile applications for children are well-designed and usable to ensure the applications are effective for children learning. This study aims to look at the usability of mobile applications designed for pre-school children especially children with speech delay. We have conducted an experiment with 10 pre-school children with speech delay and eleven of ABC and phonics mobile applications were selected based on the prior studied guidelines. During the usability testing, children's behaviour and facial expression while playing mobile applications were observed and recorded. The collected data was measured using usability measurement by analysing user's success rate. Based on the result and analysis, children have showed positive expression towards the well-designed with good usability mobile application.